EXTRACELLULAR POLYMERIC SUBSTANCE OF BIOFILMS IN THE FORMATION OF ANTIMICROBIAL RESISTANCE OF MICROORGANISMS - Kovalenko , Olexandra; Kizim , Yaroslav; Voroshylova , Natalia (The Ukrainian Scientific Medical Youth Journal, 2019)
The analysis of modern literature data on the mechanisms of the formation of antibiotic resistance and the role of extracellular polymeric substance in biofilms, which are the main form of microbial existence. The role of extracellular polymeric substance in limiting of the effect of unfavorable factors as well as the regularity and necessity of its formation for the community of microorganisms were discussed. The position on the permanent character of phenotype dispersion of microorganisms is postulated. This dispersion doesn’t provide the formation of more resistant strains only, but plays the prominent role in the permanent formation of various forms, that aren’t viable under given conditions but play the role of a depot of building material for extracellular polymeric substance. The mass death of low-resistant forms caused by the action of the antibiotic ensures saturation of the extracellular polymeric substance by dechromatized DNA, that increases the resistance of the microbial socium and contributes to the further formation of multiresistance.